KAJIAN TEORI KULTURAL DALAM KOMUNIKASI KRISIS : STUDI KASUS POLUSI UDARA KAWASAN JABODETABEK - Rahardjo, Alexandra Rianti Grandi (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2023)
The research aims to examine the phenomenon of air pollution in Jabodetabek area using cultural theory in the context of crisis communication. Air pollution is an implication of climate change which is categorized as a wicked problem because it has a broad impact on various aspects of life. Research is important because there are several cultural groups in the Jabodetabek pollution phenomenon. These various cultural groups have different perspectives regarding the urgency of air pollution. Air pollution needs to be viewed as a problem involving cultural clashes in a human system. This makes it difficult to produce an effective solution. Solutions that focus on only one group will only produce documents without execution. Thus, the government as a policy maker needs to produce a clumsy solution that can embrace all cultural groups. The research strategy is a case study and the analysis method used is a literature review. Research data is secondary data in the form of news that can be accessed freely on digital pages. The findings prove that several government policy products show that collaboration between the government, business actors and community groups can produce effective and applicable solutions. Measurably, the air quality in the Jabodetabek area is gradually improving. This research can contribute as a practical guide for policy makers in dealing with various other wicked problems.